New species of the earthworm genus Zapatadrilus (Clitellata, Acanthodrilidae) from northern Mexico - Cervantes, Gabriela; Fragoso, Carlos; Monteros, Alejandro Espinosa De Los; Sánchez-Ramos, Gerardo; Lara-Villalón, Manuel; Yañez-Pacheco, Manuel De Jesús; Lázaro-Castellanos, Jesús Omar; James, Samuel W. (Zootaxa, 2016)
Three new species of the earthworm genus Zapatadrilus are described from Tamaulipas, Mexico: Zapatadrilus aurelius sp. nov., Zapatadrilus huastecus sp. nov., and Zapatadrilus montezumensis sp. nov. Delimitation of the new species was supported by morphological and molecular (genetic distances) evidence. Diagnostic characters of the three new species include: tubulo-racemose prostates in segments 18 and 20, penial setae absent, typhlosole present and intestine beginning in 17/18. Z. montezumensis sp. nov. is separated by its metandric condition, Z. aurelius sp. nov. by the last hearts in 13 and Z. huastecus sp. nov. by the shape of the spermathecae and patterns of genital markings.